Environmental sustainability and contemporary Islamic society: A Shariah perspective - Norita Mohd Nasir,; Mahendhiran Sanggaran Nair,; Pervaiz Khalid Ahmed, (Asian Academy of Management Journal, 2022)
This paper examines the relevance of Islamic environmental theology in contemporary Islamic society. Islamic law or Shariah gives a significant prominence to environmental care. The responsibility to care for the environment is set at individual and societal levels, as outlined in the primary sources of Shariah. In line with the industrial and vast economic development, the modern jurists have extended the moral and religious obligations to firms. Environment is an important element that supports the objective of Shariah or maqasid al-Shariah, which is to safeguard the interests of all beings. However, the current devastating state of the global environment, including those of Islam-majority and Islam- dominated countries, poses major challenges to the maqasid al-Shariah. Environmental degradation is threatening the dharuriyyah level of maqasid al-Shariah, or the basic necessities of human. In view of this devastating phenomenon, this paper highlights the relevance of Islamic legal maxim of harm prevention, and how it can provide an impetus to the global environmental sustainability in modifying human attitudes and actions pertaining to the environment. We conclude that progressive interpretations of Shariah by way of incorporating vast economic development and social changes are important to address new necessities of maqasid al-Shariah. While holding on to the principles of Shariah, religious rulings pertaining to environmental matters are to be aligned to the current changing needs and problems of the society.